Physico-Chemical and Electrochemical Characterizations of a Trachyte in the Far North Region of Cameroon for Possible Electroanalytical and Environmental Purposes - Dai-Yang, Lemankréo; Pengou, Martin; Tcheumi, Hervé Leclerc; Nguihdama, Dawai; Wahabou, Abdoul; Ngatchou, Beaufils Ngana; Wamba, Odilon Romaric Tchio; Kouamo, Hervé Tchakouté; Nanseu-Njiki, Charles Péguy; Ngameni, Emmanuel (Journal of inorganic and organometallic polymers and materials, 2021)
The trachyte which was the subject of this work was subjected to physicochemical and electrochemical characterizations. X-ray diffraction, Fourier transform infrared (FT-IR), X-ray fluorescence, EDX analysis, scanning electron microscopy, cyclic voltammetry, electrochemical impedance spectroscopy were used. The physicochemical characterization have indicated the presence of elements such as Albite (Na (AlSi 3 O 8 ); Microcline (K(AlSi 3 O 8 ); Muscovite (KAl 2 (Si 3 Al)O 10 (OH) 2 ) and Diopside Aluminum (Ca(MgFeAl)SiAl) 2 O 6 ). X-ray fluorescence revealed presence of certain chemical elements in the form of oxide (SiO 2 : 65.24 wt%; Al 2 O 3 : 15.49 wt%; Fe 2 O 3 : 5.31 wt%; Ca0: 0.02 wt%; MgO: 0.01 wt%; SO 3 : 0.03 wt%; Na 2 O: 3.45 wt%; K 2 O: 5.65 wt% and P 2 O 5 : 0.029 wt%). FTIR and EDX confirmed the results obtained by X-ray and X-ray fluorescence. Presence of quartz, particles of trachyte in the form of clusters of fine aggregates and platelets in the form of rods with irregular contours was confirmed by scanning electron microscopy. Electrochemical characterization showed that our material has affinity with K 3 Fe(CN) 6 and Ru(NH 3 ) 6 Cl 3 , but this affinity is much more pronounced with K 3 Fe(CN) 6 . Modifying glassy carbon electrode with a fine fraction of the trachyte significantly increased sensitivity of the electrode of these species. SiO 2 /Al 2 O 3 ratio confirmed mechanical resistance of our material and would predestine it in the manufacture of geopolymer binders. Sum% SiO 2 + % Al 2 O 3 + % Fe 2 O 3 greater than 70 wt% indicated possibility of using material as pozzolanic materials. High level of alumina, low content of alkaline elements (K 2 O, Na 2 O) allow the use of trachyte as a raw material for manufacture of refractory products. This information would allowed us to consider the use of our material for electroanalytical, industrial purposes.